Zmiany wilgotności i temperatury wewnątrz szyszek sosny zwyczajnej (Pinus sylvestris L.) łuszczonych dwuetapowo - Aniszewska, Monika (Leśne Prace Badawcze, 2013)
Temperature measurements were taken: (1) under opening scales, (2) at the seed, and (3) in the stem, of pine cones. Changes in temperature were only examined during the second stage of a two-stage seed extraction process. During this phase a permanent dehydration temperature of 50°C was used, following comparison over a ranges of temperatures, between a lower limit of 35°C and a higher limited of 50°C. The temperature was slowest to increase in the cone’s stem, and fastest to increase under opening scales. The temperature at the seed remained constant at around 43°C for the first hour of dehydration, before increasing to 50°C. The two-stages method of cone extraction employed here, with a permanent dehydration temperature of 50°C in second stage, can be used in extraction cabinets equipped with seed extractors that allow the continuous control of air humidity. The time spent soaking during the inter-stage break should last 5 minutes. Viability of seeds obtained in two-stages process was 78% to 89%.